2022
DOI: 10.1029/2022jc018751
|View full text |Cite
|
Sign up to set email alerts
|

Upper‐Ocean Turbulence Structure and Ocean‐Ice Drag Coefficient Estimates Using an Ascending Microstructure Profiler During the MOSAiC Drift

Abstract: Sea ice mediates the transfer of momentum, heat, and gas between the atmosphere and the ocean. However, the under‐ice boundary layer is not sufficiently constrained by observations. During the Multidisciplinary drifting Observatory for the Study of the Arctic Climate (MOSAiC), we collected profiles in the upper 50–80 m using a new ascending vertical microstructure profiler, resolving the turbulent structure within 1 m to the ice. We analyzed 167 dissipation rate profiles collected between February and mid‐Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Tens to hundreds of meters beneath the transition layer, finescale parameterizations and estimates from microstructure returned eddy diapycnal diffusivity estimates ranging between 10 −7 and 10 −5 m 2 /s (Fer, 2009; Guthrie et al., 2013; Lincoln et al., 2016; Lique et al., 2014; Rainville & Windsor, 2008; Shaw & Stanton, 2014). These diffusivity values are similar to those recently obtained at depths of the transition layer from tracer observations of 10 −6 m 2 /s (Schulz et al., 2023), and consistent with weak turbulent dissipation rate estimates at these depths (Fer et al., 2022). These values are generally smaller than at lower latitudes, consistent with the finding that the surface layer stratification in the Arctic is strong and persistent, impermeable even to storm activity (e.g., Lincoln et al., 2016).…”
Section: Introductionsupporting
confidence: 91%
“…Tens to hundreds of meters beneath the transition layer, finescale parameterizations and estimates from microstructure returned eddy diapycnal diffusivity estimates ranging between 10 −7 and 10 −5 m 2 /s (Fer, 2009; Guthrie et al., 2013; Lincoln et al., 2016; Lique et al., 2014; Rainville & Windsor, 2008; Shaw & Stanton, 2014). These diffusivity values are similar to those recently obtained at depths of the transition layer from tracer observations of 10 −6 m 2 /s (Schulz et al., 2023), and consistent with weak turbulent dissipation rate estimates at these depths (Fer et al., 2022). These values are generally smaller than at lower latitudes, consistent with the finding that the surface layer stratification in the Arctic is strong and persistent, impermeable even to storm activity (e.g., Lincoln et al., 2016).…”
Section: Introductionsupporting
confidence: 91%
“…The presence of meltwater results in a very strong stratification in the uppermost meters, up to two orders of magnitude stronger compared to the halocline. Measurements with an uprising turbulence profiler also show drastically reduced turbulent mixing in the near-surface layer when meltwater layers were present Fer et al (2022). Details on the dynamics and implications of meltwater layers can be found in Smith et al (2023,2022); Salganik et al (2023a); Nomura et al (2023).…”
Section: Surface and Subsurface Layer Properties Along The Mosaic Driftmentioning
confidence: 90%
“…The thermodynamic model from Alexandrov and Nizovtseva (2008) was able to accurately describe false bottom thickness evolution (Figure 8a). Fer et al (2022) reported an average value of friction velocity of 0.47 cm s -1 for MOSAiC observations and estimated an average value of ice-ocean drag coefficient 𝐶 𝑑 as 5×10 −3 , which gives much higher average value of friction velocity of 1.65 cm s -1 , more than two times higher than measured by microstructure profiler in July. We found the best fit of in situ observations and model predictions of false bottom thickness for the average friction velocity of 0.57 cm s -1 and corresponding ice-ocean drag coefficient of 6×10 −4 .…”
Section: False Bottoms: Observations and Modellingmentioning
confidence: 91%
“…This model requires measurements of seawater temperature, salinity and friction velocity. Ice-ocean friction velocity was estimated based on the 6-hour average ice drift velocity measurements from Polarstern using ice-ocean drag coefficient 𝐶 𝑑 , while seawater physical parameters were measured by the Polarstern thermosalinograph at a depth of 11 m. The estimated values of ice-ocean friction velocity and drag coefficient were compared with in situ measurements from vertical microstructure profiler by Fer et al (2022). For false bottom modelling, the physical parameters of sea ice were taken from Alexandrov and Nizovtseva (2008).…”
Section: Ice Coringmentioning
confidence: 99%